TI_GERICHTE 12.2015.110 vom 6. Juli 2016 , Tutela giurisdizionale nei casi manifesti - prelievo di averi bancari - TI Tribunale d'appello (2016)
Tutela giurisdizionale nei casi manifesti - prelievo di averi bancari